Reimagining language learning: AI-driven innovations for engagement and growth - Bradford J. Lee (Technology in Language Teaching & Learning)
Artificial intelligence (AI) is redefining the language education industry, offering innovative solutions that enhance learner engagement, foster autonomy, improve learning outcomes, and more. This special issue explores the transformative impact of AI-driven technologies across diverse educational contexts, focusing on their applications in fostering communicative competence, ethical integration, and multimodal learning. Collectively, the thirteen articles included here also examine how AI tools can help address traditional pedagogical challenges, such as limited access to authentic communication, exam-centric curricula, and disparities in instructional quality. They highlight AI’s ability to personalize learning experiences, provide immediate feedback, and augment human interactions while preserving the essential role of educators. Other themes include strategies for tailoring AI tools to diverse linguistic and cultural contexts, fostering digital literacy and agency among learners, and developing robust evaluation frameworks for measuring AI’s long-term impact. By synthesizing insights from these contributions, this special issue sets the stage for future research, calling for ethical, inclusive, and adaptable implementations that unlock AI’s transformative potential while addressing its inherent challenges.